Efisiensi Saluran Distribusi Pada Agribisnis Peternakan - Putra, Putu Wirasanjaya; Handrito, Radityo Putro (Jurnal Kewirausahaan dan Inovasi, 2024)
This research aims to analyze efficient distribution channels to enhance marketing efficiency in catfish cultivation business at Top Fish Farm, Denpasar. Through interviews, SWOT analysis, Cost and Benefit analysis, and examination of various distribution model business, this study provides recommendations for determining the best distribution channels. The distribution channel models tested include sales to collectors, direct sales, farmers market, e-commerce, box delivery, on farm sales, and pick your own. The findings suggest that integrating several distribution models is an effective strategy to build brand and expand market. In the current production capacity, utilizing a combination of Direct Sales, E-Commerce, Box Delivery, and On Farm Sales enables Top Fish Farm to better respond to diverse market demands. Meanwhile, in business expansion with the assumption of production increasing to 100Kg per day, the primary focus is on Direct Sales to restaurants and traditional eateries, with significant emphasis on Box Delivery. This research provides a strong foundation for Top Fish Farm to design distribution strategies aligned with its business objectives, meet customer demands, and achieve sustainable growth in the fisheries industry.   Abstrak Penelitian ini bertujuan untuk menganalisis saluran distribusi yang efisien untuk meningkatkan efisiensi pemasaran pada usaha budidaya ikan lele di Top Fish Farm, Denpasar. Melalui wawancara dan analisis SWOT, Cost and Benefit dari berbagai model distribusi, penelitian ini memberikan rekomendasi untuk penentuan saluran distribusi terbaik. Model saluran distribusi yang diujikan adalah penjualan ke pengepul, direct sales, farmers market, e-commerce, box delivery, on farm sales, dan pick your own. Hasil penelitian menunjukkan bahwa integrasi beberapa model distribusi adalah strategi yang efektif untuk membangun merek dan memperluas pasar. Dalam kapasitas produksi saat ini, penggunaan kombinasi Direct Sales, E-Commerce, Box Delivery, dan On Farm Sales akan memungkinkan Top Fish Farm merespons permintaan pasar yang beragam dengan lebih baik. Sementara dalam ekspansi bisnis dengan dengan asumsi produksi meningkat menjadi 100Kg per hari, fokus utama adalah pada Direct Sales ke restoran dan warung lalapan, dengan peningkatan penting pada Box Delivery. Penelitian ini memberikan landasan yang kuat bagi Top Fish Farm untuk merancang strategi distribusi yang sesuai dengan tujuan bisnisnya, memenuhi permintaan pelanggan, dan mencapai pertumbuhan yang berkelanjutan dalam industri perikanan.